2019
DOI: 10.1024/1662-9647/a000216
|View full text |Cite
|
Sign up to set email alerts
|

Future Time Perspective and Real-Life Utterances About the Future in Young and Older Adults

Abstract: Abstract. Future time perspective (FTP) refers to an individual’s global perception of the future. It has been found to be positively related to life satisfaction. FTP is traditionally assessed via self-report, but recently a few studies have used observable behaviors for assessing FTP. We focused on two real-life behaviors (frequency and qualities of talking about the personal future) and explored whether they could be used as behavior-based measures of FTP. We examined the association between these behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In sum, in the present study, we used a new technology that has been recently applied to study memory sharing in natural social contexts (Brianza & Demiray, 2019;Demiray et al, 2018;2019) and found that cross-sectionally, older individuals in the sample demonstrated lower frequencies of autobiographical memory sharing in everyday conversations, a relationship that affected both episodic and semantic memories. For episodic memories, older age was also linked to a reduction in the level of detail at which events were described.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In sum, in the present study, we used a new technology that has been recently applied to study memory sharing in natural social contexts (Brianza & Demiray, 2019;Demiray et al, 2018;2019) and found that cross-sectionally, older individuals in the sample demonstrated lower frequencies of autobiographical memory sharing in everyday conversations, a relationship that affected both episodic and semantic memories. For episodic memories, older age was also linked to a reduction in the level of detail at which events were described.…”
Section: Discussionmentioning
confidence: 72%
“…Prior laboratorybased research has extensively studied how the sharing of autobiographical memories appears to change with older age, with one key finding being that there is a robust age-related reduction in episodic memories that is evident in both the frequency at which such memories are retrieved (Ford et al, 2014;Piolino et al, 2006;Ros et al, 2009Ros et al, , 2017 and how much episodic detail is shared to describe unique life events (Addis et al, 2008;Devitt et al, 2017;Gaesser et al, 2011;Levine et al, 2002). The present study utilized the EAR, a method that has recently been applied to capture memories being shared in everyday conversations as they happen (Brianza & Demiray, 2019;Demiray et al, 2018;2019), in order to extend the assessment of episodic specificity out of the laboratory and shed light on how older age and episodic specificity are related in the real-world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior laboratory-based research has extensively studied how the sharing of autobiographical memories appears to change with older age, with one key finding being that there is a robust age-related reduction in episodic memories that is evident in both the frequency at which such memories are retrieved (Piolino et al, 2006 ; Ros et al, 2009 , 2017 ; Ford et al, 2014 ) and how much episodic detail is shared to describe unique life events (Levine et al, 2002 ; Addis et al, 2008 ; Gaesser et al, 2011 ; Devitt et al, 2017 ). The present study utilized the EAR, a method that has recently been applied to capture memories being shared in everyday conversations as they happen (Demiray et al, 2018 , 2019 ; Brianza and Demiray, 2019 ), to extend the assessment of episodic specificity out of the laboratory and shed light on how older age and episodic specificity are related in the real-world.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the EAR has been applied to assess autobiographical sharing in natural, everyday social life, revealing outcomes that replicate and go beyond findings from the laboratory. For instance, prior work using the EAR has shown that in everyday social interactions, older adults tend to be past-oriented (Demiray et al, 2018 ) and share fewer future thoughts than young adults (Brianza and Demiray, 2019 ). Older adults also appear to share autobiographical memories in their natural social relationships for specific motives (Demiray et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%